Efficacious removal of citrate-chelated radioeuropium from aqueous solutions by adsorption onto an amorphous mesoporous silicious material: Kinetic study. (July 2019) - Mahmoud, Mamdoh R.; Rashad, Ghada M.; Soliman, Mohamed A.
Abstract: An amorphous mesoporous silicious material (AMSM) was successfully synthesized in the present study and employed as an adsorbent for studying the adsorption kinetics of Eu(III)-citrate chelates from aqueous solutions. The synthesized silicious material was characterized by X-ray diffraction (XRD), Fourier-transformed infrared spectroscopy (FT-IR), scanning electron microscope (SEM) and nitrogen adsorption-desorption isotherm. The characterization results confirmed the formation of amorphous silicate particles with spherical morphology and pore size of the mesoporous materials. Adsorption kinetics of Eu(III)-citrate onto AMSM were investigated at different pHs, Eu(III):citrate molar ratios, Eu(III) concentrations, adsorbent doses, temperatures and ionic strengths. The studied complex was efficiently adsorbed by AMSM, adsorption % > 99%, in the initial pH range 4.15–7.61. The adsorbed amount of Eu(III)-citrate was directly proportional to temperature and initial Eu(III) concentration, while slightly reduced at high ionic strength (only 10% reduction in the adsorbed amount was found at 0.1 M NaCl). At the optimum conditions, the results showed that adsorption of Eu(III)-citrate onto AMSM is a rapid process where the equilibrium is attained within 25 min. Activation energy and thermodynamic parameters for the present adsorption process were also estimated. Modeling of the experimental kinetic data of Eu(III)-citrate onto AMSM, by non-linear fitting method, clarified that the pseudo-second-order model is mostly more appropriate than the pseudo-first-order one at all the studied parameters. The excellent results of this study suggested the employment of the synthesized AMSM as an efficient adsorbent for removal of Eu(III)-citrate chelates from aqueous solutions. Graphical abstract: Image 1 Highlights: Adsorption of Eu(III)-Citrate by a mesoporous silicious material (AMSM) is studied. Removals > 99% are achieved in the pH range 4.15–7.61. Adsorption of Eu(III)-Citrate is a rapid process. The Pseudo-second-order was the best kinetic model at all the studied parameters. The results showed the efficiency of AMSM for removal Eu(III)-Citrate chelates.